2007
DOI: 10.1128/aem.01196-07
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics-Based Identification of Novel Factors Enhancing Heterologous Protein Secretion in Yeasts

Abstract: Efficient production of heterologous proteins with yeasts and other eukaryotic hosts is often hampered by inefficient secretion of the product. Limitation of protein secretion has been attributed to a low folding rate, and a rational solution is the overexpression of proteins supporting folding, like protein disulfide isomerase (Pdi), or the unfolded protein response transcription factor Hac1. Assuming that other protein factors which are not directly involved in protein folding may also support secretion of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
131
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 41 publications
(34 reference statements)
4
131
1
Order By: Relevance
“…knowledge on the Pichia chaperones is incomplete, and we here provide the complete catalog of orthologs to the S. cerevisiae endoplasmic reticulum (ER) folding machinery, which should enable more efficacious folding-system engineering in the future 26 .…”
Section: Discussionmentioning
confidence: 99%
“…knowledge on the Pichia chaperones is incomplete, and we here provide the complete catalog of orthologs to the S. cerevisiae endoplasmic reticulum (ER) folding machinery, which should enable more efficacious folding-system engineering in the future 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gasser et al (10) identified, by transcriptomic analysis, new S. cerevisiae helper factors improving heterologous protein secretion as efficiently as, or even more efficiently than, known candidates. In particular, the overproduction of Cup5p, the subunit c of the yeast vacuolar (H ϩ )-ATPase (V 0 domain), increased the secretion of a human antibody Fab fragment as much as Pdi1.…”
Section: Discussionmentioning
confidence: 99%
“…In eukaryotic cells the focus has been more on the ability of chaperones to reduce the cell toxicity of polyQ and asynuclein aggregates linked with the occurrence of neurodegenerative diseases such as Huntington and Parkinson (Auluck et al, 2002;Cummings et al, 2001;Muchowski and Wacker, 2005;Willingham et al, 2003). Fewer studies (Damasceno et al, 2007;Gasser et al, 2007;Smales et al, 2004) have examined the consequences of manipulation of the chaperone network in the context of recombinant protein production in cultured cell lines.…”
Section: Introductionmentioning
confidence: 98%